Complicated multiple organ infection of Purpureocillium lilacinum and varicella-zoster virus infection in a patient with Evans' syndrome. Issue 2 (April 2022) - Hu, Xiangrong; Zhang, Li; Lin, Qingsong; Zhang, Fengkui; Zhao, Xin
Abstract : Abstract: Purpureocillium lilacinum ( P lilacinum) is a rare pathogenic fungus, which mainly involves immunocompromised individuals. Here, we report a case of complicated multiple-organ infections involving skin, lungs, and spleen in a 63-year-old female with Evans' syndrome after 9 months of glucocorticoid treatment. Microbial examinations of skin biopsy and blood samples revealed P lilacinum infections. Posaconazole was effective in this patient. During anti-fungi treatment, she developed varicella-zoster virus infection and was diagnosed through next-generation sequencing examination. In conclusion, P lilacinum may affect different organ systems and is susceptible to posaconazole treatment. The molecular-based methods like microbial cell-free DNA sequencing could provide accurate and timely identification of a wide range of infections.